2014
DOI: 10.1016/j.jpowsour.2013.10.148
|View full text |Cite
|
Sign up to set email alerts
|

Stability of carbon nanofibre-supported platinum catalysts in the presence of chloride under controlled mass-transfer conditions

Abstract: The effect of chloride on the stability of platinum electrocatalysts was studied by rotating disk measurements in sulfuric acid electrolyte with a continuously increasing concentration of chloride anions. The activity towards oxygen reduction was found to be reduced by a factor of seven when 140 ppm chloride was present. Platinum corrosion was severe at high potentials, presumably accelerated by potential cycling, and greatly enhanced by mass transport. A five-fold increase in corrosion rate was found when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…[8][9][10][11] On the other hand, chloride promotes platinum corrosion, 12 especially under potential cycling conditions. 7,13 The platinum that is dissolved during corrosion can then redeposit inside the PEMFC membrane 14 or on the top of the catalyst film, as demonstrated in ex situ RDE experiments. 15 In this work we show, for the first time, that chloride not only enhances the corrosion rate but essentially changes the corrosion mechanism when compared to a non-chloride environment.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[8][9][10][11] On the other hand, chloride promotes platinum corrosion, 12 especially under potential cycling conditions. 7,13 The platinum that is dissolved during corrosion can then redeposit inside the PEMFC membrane 14 or on the top of the catalyst film, as demonstrated in ex situ RDE experiments. 15 In this work we show, for the first time, that chloride not only enhances the corrosion rate but essentially changes the corrosion mechanism when compared to a non-chloride environment.…”
mentioning
confidence: 98%
“…S3a and b (ESI †) reveals that the potentiostatic stress test is much less damaging (less Pt gets removed) than the potentiodynamic test -with or without the presence of Cl À -which is consistent with the literature. 2,5,13 In conclusion, a combination of cyclic voltammetry, flow system and on-line ICP-MS platinum concentration measurements (EFC-ICP-MS) was used to study the potentiodynamic corrosion of commercial Pt/C electrocatalysts in perchloric acid in the presence of Cl À . It was shown that chloride affects the platinum corrosion in three ways.…”
mentioning
confidence: 99%
“…[16] To palov et al also showedt hat the dissolution of Pt in an acidic electrolyte occurs mainly during the cathodic scan. [14a] Parameters that have been suggested to accelerate Pt dissolution are low pH values, [14a, 17] high potentials, [7a, 14a, 18] hight emperatures, [19] the presence of Cl À ions, [10,19,20] O 2 - [21] or CO-saturated electrolytes, [22] and potential-dynamic conditions. [23] It is important to mention that most dissolution studies of platinum have been performed on bulk metal.…”
Section: Introductionmentioning
confidence: 99%